Territori ad alta energia Governo del territorio e pianificazione energetica sostenibile: metodi ed esperienze - Fanfani, David; Fagarazzi, Claudio (Territori, 2012)
In recent years the subject of energy planning has come to occupy a role of growing importance, both in relation to the escalating costs, scarcity and impact of energy procurement and consumption and in relation to the increasingly broad future prospects generated by the development of technologies for the exploitation of renewable sources. Within this framework, the development and use of the latter frequently appears to be without benchmarks for integration into the broader picture of territorial planning, and hence of coordination with other human activities and territorial resources. With this in mind, this book aims to compose the elements of a perspective in which energy planning is seen not as an ulterior and separate form of planning, but as an activity integrated within the more general instruments for the government of the territory, and more specifically one that employs the resources of the territory in a sustainable manner also with a view to endogenous local development.